2017
DOI: 10.1097/qai.0000000000001499
|View full text |Cite
|
Sign up to set email alerts
|

HIV Viral Load Suppression in Adults and Children Receiving Antiretroviral Therapy—Results From the IeDEA Collaboration

Abstract: Background Having 90% of patients on antiretroviral therapy (ART) and achieving an undetectable viral load (VL) is one of the 90:90:90 by 2020 targets. In this global analysis, we investigated the proportions of adult and paediatric patients with VL suppression in the first three years after ART initiation. Methods Patients from the IeDEA cohorts who initiated ART between 2010 and 2014 were included. Proportions with VL suppression (<1000 copies/mL) were estimated using: (i) strict intention-to-treat (ITT) –… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
49
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 29 publications
8
49
4
Order By: Relevance
“…Previous studies have reported that the younger age is associated with poor antiretroviral adherence and viral load suppression [25][26][27]. Among factors put forward to be responsible for the unfavourable outcomes included higher CD4 count prior to HAART intervention [26] and delayed HAART initiation [27]. In contrast to our study, we observed statistically no clear pattern in the rate of viral suppression with respect to the various age groups (Tables 2 and 3).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that the younger age is associated with poor antiretroviral adherence and viral load suppression [25][26][27]. Among factors put forward to be responsible for the unfavourable outcomes included higher CD4 count prior to HAART intervention [26] and delayed HAART initiation [27]. In contrast to our study, we observed statistically no clear pattern in the rate of viral suppression with respect to the various age groups (Tables 2 and 3).…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies have reported that the younger age is associated with poor antiretroviral adherence and viral load suppression [25][26][27]. Among factors put forward to be responsible for the unfavourable outcomes included higher CD4 count prior to HAART intervention [26] and delayed HAART initiation [27].…”
Section: Discussionmentioning
confidence: 99%
“…The unusual mortality pattern in North America (lower than in other concentrated epidemic settings at early ART durations, but higher at later durations) is consistent with previous inter-regional comparisons [31,39], and could be partly because patients are only included in the North American database if they have at least two visits in the year of enrolment [40], implying a selection bias due to the exclusion of individuals who die or transfer care before their second visit. The higher rates of mortality in North American patients compared with Asian patients, at longer ART durations, is consistent with a recent analysis that found significantly lower viral suppression in North American patients compared with Asian patients [41]. This may be due to the nature of the American healthcare system, with patients frequently transferring between public and private care, and the resulting instability in care contributing to higher long-term mortality [42].…”
Section: Discussionsupporting
confidence: 87%
“…Viral load testing is the preferred method for monitoring patients on ART, as treatment failure is identified earlier and more accurately than CD4 cell count monitoring [5,36].…”
Section: Discussionmentioning
confidence: 99%